SISTEM INFORMASI MANAJEMEN DALAM ORGANISASI : KONSEP DASAR, EVOLUSI, DAN PERANANYA DI ERA DIGITAL - Octa Romadhona Putri; Saipul An-Nur; Ade Rosad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Management Information Systems (MIS) are the backbone of organizations in the digital era because they provide accurate, relevant, and timely information for management in decision-making, planning, and control. This paper reviews thebasic concepts of MIS, its evolution from a data processing system to an integrated digital-based system, and its strategic role in supporting organizational effectiveness. This article draws on recent literature from the past five years to demonstrate how developments in digital technology have transformed the role ofMIS from an administrative tool to a strategic organizational asset